Longitudinal analysis of electroencephalography pattern changes in an infant with Schaaf‐Yang syndrome and a novel mutation in melanoma antigen L2 (MAGEL2). Issue 6 (28th March 2022) - Mizuno, Shinsuke; Yokoyama, Koji; Yokoyama, Atsushi; Nukata, Takayuki; Ikeda, Yuka; Hara, Shigeto
Abstract: Background: Schaaf‐Yang syndrome (SYS) is a rare hereditary disease caused by truncating point mutations of the paternal allele of melanoma antigen L2 ( MAGEL2 ), one of five protein‐coding genes within the Prader‐Willi syndrome (PWS) critical domain. SYS shares many clinical and molecular characteristics with PWS but has some distinct features, such as joint contractures and autism. Patients with PWS show abnormal electroencephalography (EEG) patterns. However, there are very few reports on EEG findings in patients with SYS. Methods: A SYS patient was included in this study. Detailed neurological examinations and EEG were performed from neonate to infant ages. Sanger sequencing was performed. Results: Our patient presented abnormal EEG findings and had diffuse brain dysfunction symptoms including a reduced level of consciousness, diminished spontaneous movements, hypotonia, feeding difficulties, and hypoventilation from early after birth. As she grew older and her background activity of EEG normalized, her neurodevelopmental symptoms remained but improved. Sanger sequencing of this patient revealed a novel, heterozygous c.2005C > T, truncating mutation in the MEGAL2 gene. Conclusions: We described an SYS‐associated, time‐dependent, EEG pattern in a patient with SYS. Our findings of longitudinal EEG changes in a patient with SYS revealed a specific pattern of how affected individuals develop brain function. Abstract : We describe a Schaaf‐Yang syndrome‐associated, time‐dependent, EEG pattern. Sanger sequencing of this patient revealed a novel, heterozygous c.2005C>T, truncating mutation in the MEGAL 2 gene. Our findings of longitudinal changes in EEG in a patient with Schaaf‐Yang syndrome showed a specific pattern of how affected individuals develop brain function.